Analyzing the Mediation Impact of Teacher Job Satisfaction on Teacher Performance: The Role of Teacher Certification and Organizational Culture - Sembiring, Rasmulia; Danilwan, Yuris; Sofiyan, Sofiyan; Sherly, Sherly; Sudirman, Acai (FKIP Universitas Lampung, 2022)
Analyzing the Mediation Impact of Teacher Job Satisfaction on Teacher Performance: The Role of Teacher Certification and Organizational Culture Objectives:This study aims to analyze the mediating impact of teacher job satisfaction on teacher performance with teacher certification and organizational culture as predictors. Methods: This study uses a quantitative approach with PLS-SEM analysis. The sampling technique is oriented to purposive sampling, so the total sample acquisition is 215 teachers of Civil Servants (PNS). Findings: The results of this research suggest that teacher certification and organizational culture have a positive and significant effect on teacher job satisfaction and performance. This research also confirms that teacher job satisfaction significantly mediates the relationship between teacher certification and organizational culture on teacher performance. Conclusion: This study concludes that teacher certification will create better teaching resources. A strong organizational culture has the power to turn teachers into advocates. Satisfied and certified teachers and strong organizational culture will encourage increased performance.Keywords: principal supervision,compensation,teacher job satisfaction, organizational citizenship behavior, teacher performance.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202233